School closures in Chile: access to quality alternatives in a school choice system - Elacqua, Gregory; Martínez, Matías; Santos, Humberto; Urbina, Daniela (Estudios de Economía, 2012)
In this paper, we analyze the schooling alternatives of families that could face school closure. This article identifies, characterizes, and georeferences the institutions classified as low-performing by the SEP Law along with their closest alternatives. The findings indicate that a significant number of families do not have any quality alternatives nearby, particularly families in rural areas and/or in schools with a high percentage of low SES students. Additionally, when admissions barriers and family preferences are incorporated in the analysis, school alternatives are considerably reduced. Alternatives are further reduced when using a more stringent definition of school quality.